Asteraceae endémicas del Perú - Beltrán, Hamilton (2006)
The Asteraceae are the second most diverse family in the Peruvian flora, with approximately 250 genera and 1590 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Most Peruvian Asteraceae are herbs, shrubs and subshrubs. Here we recognize 724 endemic taxa, 695 at the species level and 29 varieties. The most species-rich genera are Senecio, Gynoxys and Verbesina. This family includes 11 genera endemic to Peru: Ascidiogyne, Aynia, Bishopanthus, Chucoa, Ellenbergia, Hughesia, Notobaccharis, Pseudonoseris, Schizotrichia, Syncretocarpus, and Uleophytum. Endemic taxa are mainly found in the Mesoandean, Pluvial Montane Forest and Very Humid Montane Forest regions, from sea level to above 4000 m. We assigned the IUCN categories and criteria to 567 taxa. Eightysix species (approximately 12% of all endemic Asteraceae) have been registered in a protected area.